Hubungan Pola Makan dengan Kejadian Anemia pada Remaja Putri di SMK Batik 2 Surakarta - Widyaningrum, Restu; Setiyaningrum, Zulia (Universitas Batanghari Jambi, 2024)
This study aims to determine the relationship between diet and the incidence of anemia in young women at SMK Batik 2 Surakarta. This research uses the Observational Analytical method with a Cross-Sectional approach. The sample consisted of 9 classes selected using the Proportional Random Sampling technique with inclusion criteria, namely young women who were not menstruating and not on a diet, with a total of 60 respondents. Dietary pattern data was obtained through interviews using the Food Frequency Questionnaire (FFQ) form for the past month, then dietary patterns were determined based on food consumption scores. Hemoglobin (Hb) levels in adolescent girls were measured using the Cyanmethemoglobin method with the help of health workers. Data were analyzed using the Kolmogorov-Smirnov normality test and the relationship between variables was tested using the Pearson Product Moment correlation test. The results of the study showed that there was a significant relationship between diet and the incidence of anemia in young women at SMK Batik 2 Surakarta. Apart from that, this research also found that teenage girls with poor diets had a 0.004 times greater chance of experiencing anemia compared to teenage girls who had good diets.